QUALITY OF WELLNESS SERVICES IN THE NORTH GREAT PLAIN REGION - Péter Hidvégi; Melinda Biró; Andrea Lenténé Puskás; András Tatár; Kinga Bárdos; József Márton Pucsok (University of Debrecen, Institute of Sport Sciences, 2019)
Wellness is the philosophy of life in everyday life. In a holistic sense, it is also used as a harmony of physical, mental, and spiritual abilities, basically means prevention, regeneration, relaxation, and fitness. The investigation took place between September and December 2018. Of the 166 participants, 94 were women, and 72 were men. As a result of the research, we can state that respondents are looking for relaxation and relaxation in wellness hotels. Their expectations are related to their age, place of residence, and family status.